If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2n + 4(48.75 + -5n) = 195 2n + (48.75 * 4 + -5n * 4) = 195 2n + (195 + -20n) = 195 Reorder the terms: 195 + 2n + -20n = 195 Combine like terms: 2n + -20n = -18n 195 + -18n = 195 Add '-195' to each side of the equation. 195 + -195 + -18n = 195 + -195 Combine like terms: 195 + -195 = 0 0 + -18n = 195 + -195 -18n = 195 + -195 Combine like terms: 195 + -195 = 0 -18n = 0 Solving -18n = 0 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Divide each side by '-18'. n = 0 Simplifying n = 0
| f(-1)=4x-10 | | -5y=8x-4 | | -5x=8x-4 | | h(-2)=x^2-9 | | 7x-26=-89 | | ln*3+ln*(x-5)=ln*x | | X^5+11x^3+30x=0 | | 4+x=9*3 | | 2/-7 | | 5(u+8)-8u=22 | | 180=(3x+8)+(7x-18) | | 1+x=-2*8 | | 3(3n+4)=36+6n | | 0.5(8k+2)=17 | | 7+5ln(x)=2 | | (3b+2r)+(4b+r)= | | H=(6x-10) | | h(10)=x^2-9 | | 16f+4g= | | -45=-4x+11 | | 160=-8p-5(1+5p) | | 4(t+u)=19 | | 14x+18=126 | | X^2/-2 | | -3+x=-8*-3 | | 2(1.3-3)=2.6-5 | | .75x=350000 | | .4*x=38 | | X^2/10 | | 9(3-2x)=2(-8+10) | | 11x^2-82x+147=0 | | (3x+17)+(x-23)=9 |